Evaluation of dry matter accumulation of maize (Zea mays L.) hybrids - Bodnár, Karina Bianka; Nasir Mousavi, Seyed Mohammad; Nagy, János (Acta Agraria Debreceniensis, 2018)
The increase of the grain yield of maize is closely correlated with its seasonal dry matter accumulation. Dry matter is accumulated into the grain yield during the grain filling period. The following maize hybrids were involved in the experiment: Armagnac FAO 490, Loupiac FAO 380 and Sushi FAO 340. In order to determine dry matter content, two samples per week were taken on the following days: 22nd, 25th, 28th, 31st August, 4th, 7th, 14th, 18th, 22nd, 25th, 29th September and 2nd, 6th, 9th, 13th October. In the course of sampling the weight of 100 grains from the middle section of 4 ears was measured in 4 replications. Dry matter content was determined after drying to constant weight in a drying cabinet at 60 °C. Harvesting was performed on 13th October 2017. The daily precipitation sum was determined by local measurements, while the daily radiation and temperature data were provided by the Meteorological Observatory Debrecen of the National Meteorological Service in Budapest. Among the agrometeorological parameters, an analysis was made of the precipitation during the growing season, effective heat sums during the vegetative and generative phase, and the water supplies. The daily heat sums were determined using the algorithm proposed. The amount of precipitation in the winter period before the 2017 growing season was 210 mm. The soil was saturated until its field capacity. The rather dry and warm March and April had a favourable effect, but there was no worthy amount of precipitation until May (51 mm) due to the condition of the dried seedbed. Sowing was performed on the 5th of May 2017 in a randomised small plot experiment. There was favourable precipitation and temperature during the growing season, thereby providing ideal conditions for maize development, growth and yield formation. There was near average amount of precipitation in each year. The total amount of precipitation in the summer period is 342 mm. Temperature was mostly above the average, but there was no long and extremely warm period. The Armagnac hybrid reached its highest dry matter mass 126 days after emergence. Physiological maturity was reached sooner (on the 119th day) in the case of Loupiac, and even sooner in the case of Sushi (116th day). The thousand grain weight of Sushi (which has the shortest ripening period) was 286 g at the time of physiological maturity, while that of Loupiac was 311 g. Compared to Sushi, Armagnac showed 12 g more dry matter accumulation (306 g). In the case of all three examined hybrids, physiological maturity was preceded by an intensive phase, when the dynamics of dry matter accumulation was rather quick. On average, Sushi gained 2.8 g dry matter per day between 103 days following emergence and physiological maturity, while the same values were 3.2 g for Armagnac and 3.3 g for Loupiac. The aim of the regression line slope is to predict the behavior of the dependent variable with the knowledge of the values and characteristics of the independent variables using the regression line equation. Furthermore, to determine how the location affected the dynamic of dry matter accumulation in the Armagnac, Loupiac and Sushi hybrids. In regression analysis, the coefficient of explanation showed that the effect of day in the Armagnac was 97%, in the Loupiac 94%, in the Sushi 90 %. The determination coefficient (R2) is useful in determing how the regression equation fits. But, as we have seen, the determination coefficient alone is not sufficient to verify the model’s accuracy, in addition to the determination coefficient (R2), the normality of the data or the residuals, the variance of the variables at different levels, the independence of the data relative to time and non-oblique. Observations are evaluated for the correctness of the fitted model. Dry matter values decreased evenly and slightly following physiological maturity. According to our research results, it was established that physiological maturity is followed by a moderate dry matter loss. Until harvesting, Armagnac lost 40 g of its thousand mass weight in 29 days, while the same value pairs were 69 g in 36 days for Loupiac and 29 g in 39 days for Sushi. Loupiac – which had the highest weight at the time of physiological maturity – lost the most of its dry weight; therefore, Armagnac and Sushi had higher values at the time of harvesting.